Assessment of Quality Status of Zinc Sulfate (hepta hydrate) Fertilizers Available in the Markets of Jessore Sadar Upazila - Islam, GMM; Hossain, M; Iqbal, SMA; Mollah, MRA (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted in the Department of Soil Science, Bangladesh Agricultural University, Mymensingh during January to December, 2012 to see the quality status of Zinc Sulfate (hepta hydrate) fertilizers available in the markets of Jessore sadar upazila. For this purposes Zinc Sulfate (hepta hydrate) fertilizer samples were randomly collected from all union of the upazila. Fifteen unions and a pourashava in this upazila were included the experiment. Three composite samples were collected from each of the unions. Therefore, 48 composite samples were ready for 16 unions including pourashava. In this study 79% Zinc Sulfate (heptahydrate) fertilizer was adulterated and 21% was qualified according to government specification. 40% of them were ten to fifty percent of required Zn content and 2% of them were same level of S content. Only 21% of total fertilizers contained hundred percent of required Zn. Whereas, 96% fertilizers contained the same level of required S and only four percent of the fertilizers was found as sulfur deficient. The highest nutrient value of S and Zn were 17.75% and 23.03% respectively. On the other hand, the lowest value of them was 5.2% and 1.30%. Further 27% of them contained above eighty percent of required Zn. No unique relation between sulfur and zinc content of those fertilizers was found. J. Environ. Sci. & Natural Resources, 8(1): 69-71 2015